Situação nutricional e alimentar de portadores de Malária residentes no Amazonas - Brasil - Alencar, Fernando Hélio; Yuyama, Lucia Kiyoko Ozaki; Gutierrez, Miriam Elenit Lima (Acta Amazonica, 2001)
Two hundred sixty-eight subjects (198 men and 70 women) with blood-smears positive for malaria parasites, diagnosed at the Fundação Nacional de Saúde in Manaus were studied. The antthopometric evaluations of weight, height, body mass index, triceps skinfold thichness, brachial circunference and arm muscle circunference were performed an all subjects. Haematological and biochemical evaluations were performed for 121 individuals and coprological examination for parasites for 55. Despite the malaria and precarious living conditions of the patients, the anthopometric mean values were normal with the exception of triceps skinfold thickness, which was below normal. Measures of haematocrit, haemoglobin, glicose, serum iron and triglycerides were within the normal range, with total protein at the lower limit of the recomended range, and HDL cholesterol below the limit of normality. The dietary investigation revealed that the study population had acess to a well balanced diet, with frequent consumption of proteinrich food (fish, meat and eggs), abundant sources of energy (rice, bread and vegetable oil) and smalles quantities of regulators (green vegetables and fruits). Among factors aggravating the nutritional status of the malaria patients, a high incidence of multiple gastrointestinal parasitosis, precarious living conditions, low educational status, low income and high consumption of tobacco and alcohol were detected.
Nutritional and dietary status of individuals with Malaria resident in Amazonas State - Brazil.
Keywords: Nutritional Status; Malaria; Plasmodium; Estado Nutricional; Malária; Plasmodium